Integrasi Sistem Majaemen Tata Usaha Dengan Metode Service Oriented Architecture (SOA) Pada SMP Negeri 10 Mataram - Jaka Bagus Wijanarko; Royana Afwani; Moh. Ali Albar (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2019)
The Business processes of SMP Negri 10 Mataram keep changing due to the organization’s necessity, so the development of existing systems and applications is needed. For the complex cases, they need to integrate the systems and applications to deliver the effective and good quality of educational processes and activities. SMP Negeri 10 Mataram has several problems: until these time in every administrative section do their processes business or their task manually, that is not efficient especially in term of time for work, and more there are no relatable things between every section. By this research to resolve these problems, the administrative management system integration was developed by using the Service Oriented Architecture (SOA) method. Service-Oriented Architecture (SOA) is one of many ways to design data integration from several different systems. Service-Oriented Architecture (SOA) is a software development technology architecture with a service approach, allowing the relationship and exchange of data or information between every systems and application to be much easier. In this research, the SOA analysis and design process was conducted at SMP Negeri 10 Mataram and obtained six services, namely: service administrator, financial service, staffing service, student service, infrastructure services, library service.